Literatur Review Efektivitas Kompres Hangat Terhadap Dismenore Remaja Putri - Fajrin, Irmasanti; Losu, Fredrika N; Dimalaya, Devianti (JIDAN Jurnal Ilmiah Bidan, 2022)
Background :Warm compresses are a method of giving a feeling of warmth to teenagers who experience menstrual pain by using a tool that creates warmth in the parts of the body that need it. Warm compresses that use the principle of heat transfer by means of conduction, namely by attaching a warm towel to the area above the symphysis, will improve blood circulation and reduce muscle tension, thereby reducing pain in young women. The warm compress technique is carried out by giving bottles filled with water to young women who are having menstrual pain. Purpose : This study was to examine literature, articles and research documents which identified the effect of warm compresses on dysmenorrhea in young women. Method : type of research is literature review namely a research review literature the results of previous research studies to obtain data in accordance with the topic. The researcher conducted a journal search using 3 databases namely google scholar,pubmed andproQuest by using keywords, the journals you are looking for are from 2015-2021 and researchers get 10 literature which is used for literature review. Results : Journal studies show that there is an effect of giving warm compresses to young women, warm compresses are an effective intervention to reduce menstrual pain (dysmenorrhea) in adolescents apart from the use of pharmacological drugs. These results are expected to provide a reference in evidence-based midwifery interventions and add insight, especially to midwives and young women at the time of menstruation in order to achieve the target of reducing pain